Quantum tunneling and Aschenbach effect in nonlinear Einstein-Power-Yang-Mills AdS black holes - Sucu, Erdem; Sakalli, Izzet (Iop Publishing Ltd, 2025)
This study explores the thermodynamics, quantum tunneling phenomena, and unique orbital properties of Einstein-Power-Yang-Mills (EPYM) black holes embedded in Anti-de Sitter (AdS) spacetimes, highlighting the role of the nonlinear Yang-Mills (YM) charge parameter gamma. We derive explicit expressions for the black hole metric, horizon structure, and associated thermodynamic quantities, including Hawking temperature and phase transitions. Using the WKB approximation and Hamilton-Jacobi formalism, we investigate the quantum tunneling of massive bosons, revealing how nonlinear YM interactions significantly alter the radiation spectrum and emission rates. We analyze the effective potential for scalar field propagation, showing that nonlinear YM effects produce distinctive modifications in potential barriers and radiation emission processes. Additionally, our study reveals the presence of the Aschenbach effect, typically exclusive to rotating black holes, in static and spherically symmetric EPYM black hole solutions.
Keywords: black hole; Yang-Mills; radiation emission; effective potential; quantum tunneling; photon orbits; aschenbach effect